Yeasts in traditional Baijiu fermentation: diversity, functions, microbial interactions and applications - Dong, Weiwei; Peng, Yaxuan; Ma, Jiyuan; Hu, Yuanliang; Chen, Shenxi; Zhao, Shumiao (Frontiers in Microbiology, 2025)
Baijiu is a traditional distilled liquor unique to China. Its distinctive flavor is shaped by the synergistic activity of complex microbial communities, among which yeasts play a central role in sugar metabolism, ethanol fermentation, and aroma synthesis. In recent years, the advancement of isolation and cultivation techniques, high-throughput sequencing, metagenomics, and multi-omics technologies has deepened our understanding of yeast community compositions, succession patterns, and functional characteristics during Baijiu brewing. Among these, Saccharomyces cerevisiae was recognized as the core ethanol-producing species and has been extensively studied for its metabolic traits and stress tolerance in Baijiu fermentation. Studies have shown that, in addition to S. cerevisiae, non-Saccharomyces yeasts such as Pichia, Wickerhamomyces, Saccharomycopsis, Kazachstania, and Candida et al. are widely distributed across strong-, sauce-, and light-flavor Baijiu and their respective starters (Daqu), exhibiting robust ester-producing capacities and stress resistance. These yeasts occupy distinct ecological niches throughout fermentation stages and engage in dynamic and environment-dependent interactions with lactic acid bacteria, molds, and other microbes. This review systematically summarizes yeast diversity, community structure, metabolic traits, key functional genes, microecological interactions, recent discoveries of novel yeast species, and advances in genetic engineering in Baijiu brewing. It further highlights future research priorities, including multi-omics integration, functional exploration of non-Saccharomyces yeasts, and synthetic biology-guided strain development, with the goal of supporting high-quality and intelligent Baijiu production.